EXPERIMENTAL INVESTIGATION OF LAMINAR MIXED CONVECTION IN AN INCLINED ANNULUS (Journal of Engineering, 2006)
Experiments were carried out to study the local and average heat transfer by mixed convection to a simultaneously developing air flow in a horizontal inclined, and vertical concentric cylindrical annulus. The experimental setup consists of an annulus has a radius ratio of 0.555 and inner cylinder with a heated length 1.2m subjected to the constant heat flux while the outer cylinder is subjected to the ambient temperature. The investigation covers Reynolds number range from 154 te 845, heat flux varied from 96 W/m² to 845 W/m², and annulus angles of inclinations a (horizontal), 40°, 70°, and 90° (vertical). Results demonstrate the temperature variation along th inner cylinder surface and the local Nusselt number Nu, variation with the dimensionless axia distance, for all angles of inclinations which shows an increase in the Nu, values as the heat fit increases and as the angle of the inclination moves from the vertical to the horizontal position